A descriptive study of COVID-19 at a tertiary care hospital - Mittal, Amit; Singh, Manoj Kumar; Kumar, Rajeev; Mandsorwale, Deepti (ScienceRise: Medical Science, 2021)
Coronavirus disease 2019 (abbreviated “COVID-19”) is an emerging respiratory disease that is caused by a novel coronavirus and was first detected in December 2019 in Wuhan, China. The cases of COVID-19 infection since then were showing increasing trend in all over the world. The aim: to study the epidemiological distribution and determinants of COVID-19 pandemic. Methods: it is a descriptive study carried out at a tertiary care hospital of India. The population comprised of patients admitted in the hospital. Sample size comprised of all the subjects admitted in the hospital with established COVID 19 +ve cases. The duration of study was April 2020 to June 2020. The study was approved by the Institutional Ethical committee and Informed consent was obtained from each subject before the conduct of the study. Data collection was done by a pre-structured questionnaire. Data entry and analysis was done using SPSS version 20 software. Results: out of total 38 COVID-19 +ve cases, 95 % were male and 5 % female ant the maximum numbers of cases ranges between 36–40 years of age group with the median age of 32 years.53 % of cases were Muslim and 47 % Hindu by religion. The median duration of stay in hospital of all COVID-19 +ve cases was11 day that on further differentiation with co-morbidity was 15 days and 11.5 without any co-morbidity. The median duration taken between 1st sample taken and report provided was 2 days, between 2nd sample taken and report provided 1 day and between 1st and 2nd sample taken was 11 days. Conclusions: present study concluded that middle age persons were affected in majority which may be due to more exposure to public places. Co-morbidities are strong predictors of requirement for admission and duration of stay at hospital